2019
DOI: 10.1097/bpo.0000000000000978
|View full text |Cite
|
Sign up to set email alerts
|

Control of Walking Speed in Children With Cerebral Palsy

Abstract: Diagnostic level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…Moreover, walking speed was found to be positively correlated with subjective gait scores across the entire cohort ( r =0.41, p =0.001). This parameter has a direct impact on patient autonomy and is one of the most important function‐related parameters . Jasper et al likewise reported that walking speeds had an impact on the QoL of children with CP .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, walking speed was found to be positively correlated with subjective gait scores across the entire cohort ( r =0.41, p =0.001). This parameter has a direct impact on patient autonomy and is one of the most important function‐related parameters . Jasper et al likewise reported that walking speeds had an impact on the QoL of children with CP .…”
Section: Discussionmentioning
confidence: 99%
“…Players must effectively move to utilize strength, speed, power, agility, balance, flexibility, and endurance [36]. The ability of players to control speed is essential for the gait of various activities [26]. Speed has different characteristics in each other movement [22].…”
Section: Discussionmentioning
confidence: 99%
“…Players need speed and agility to run, rotate, change direction, dribble, or face an opponent. Efforts to increase speed for children with CP are required [26] Improving the speed and agility of CP Football players requires a proper training model to suit your needs. The training program must be modified for each player to optimize maximum performance in matches [27].…”
Section: Introductionmentioning
confidence: 99%
“…Yürüme hızı günlük yaşamda birçok fonksiyonel ve sosyal aktivite için önemlidir. SP'li olgularda yürüme hızının kas zayıflığı ile ilişkili olarak azaldığı ifade edilmiştir (25). Literatürde SP'li olgularda yürüme fonksiyonu ile gövde kas kuvveti arasındaki ilişkiyi inceleyen tek bir çalışmaya rastlandı.…”
Section: İstatistiksel Analizunclassified